Institution of declaring a person dead in Poland in the interwar period - Orzechowska, Agnieszka; Orzechowski, Tomasz (Studia Iuridica Toruniensia, 2017)
The subject of the article is presenting solutions in the scope of the institution of declaring a person dead, existing at the territory of the Republic of Poland after regaining independence in 1918. This matter was regulated on grounds of two models: a French model emphasising protection of interests of a missing person by cost of a complicated and long-term proceedings, exemplified on the Napoleon’s Code and a German model assuming a fast and efficient explaining of the situation of a missing person and his/her relatives after lapse of a period determined in a statute, decidedly closer to the 20th century science. In the paper there was carried out analysis of provisions obliging at the territory of particular partitions, thus the Civil Code of the Congress Kingdom of Poland including the novelising act of 27 January 1922, then Russian civil law based on volume 10 of Zwod of Laws of the Russian Empire, through regulations of the Austrian civil code Allgemeines bürgerliches Gesetzbuch (ABGB) in force at the territory of Galicia, ending on the universal German civil code (BGB). The Authors complementarily borrow information not only from legal norms contained in legal systems of the European states but also from judicial decisions of courts, among others of the RP Supreme Court.